Study of Naskh Verses According to Nawawi Al-Bantani and Quraish Shihab: دراسة آية النسخ عند نووي البنتاني و قريش شهاب - Rahman Hakim; Nahdliyyatul Azimah (Ar-Rasikhin : Jurnal Ilmu Al-Qur'an dan Tafsir, 2025)
This study highlights the root of the nasakh problem in the Koran, namely Q.S. al-Baqarah verse 106. Different viewpoints on the interpretation of this verse have different legal consequences; If the meaning of 'âyah' in this verse is interpreted as a verse from the Qur'an, then the consequence is that in the Qur'an there is a verse that has been deleted by law even though the reading is still there. However, if it is interpreted as 'previous Shari'a', then all verses of the Koran remain valid and none of them are abrogated. The aim of this research is to examine the cross-opinions of Al-Qur'an scholars regarding the nasakh. The author applied the comparative method (muqârin) and a qualitative approach through literature review in this research. The result is that there are significant differences between the interpretations of Nawawi al-Bantani and Quraish Shihab in understanding this verse, which also causes differences in understanding other verses of the Koran.